Novel kraft-lignin-based adhesives for the production of particleboards - Nemec, Miroslav; Prokůpek, Luboš; Obst, Vojtěch; Pipiska, Tomas; Kral, Pavel; Hysek, Stepan (Elsevier Science, 2024)
Lignin is produced worldwide in pulp mills and is currently mainly used for energy recovery. Because of its chemical properties, one possible utilisation is the production of lignin-based materials. Currently, developed lignin-based adhesives are based mainly on lignosulfonate instead of kraft lignin since lignosulfonate is more reactive than kraft lignin. However, worldwide substantially more kraft lignin is produced. The presented research deals with the development of resin chemically modified with kraft lignin up to 40% (w/w) content of kraft lignin. The synthesis of adhesives is described, and developed adhesives are characterised. Namely, viscosity, mechanical properties of resins and results of differential scanning calorimetry are presented. Furthermore, the developed kraft-lignin-based adhesives were used for the production of particleboards. Pre-pressing in a cold press followed by hot pressing in a laboratory press was used for the production of particleboards. The physical (thickness swelling, moisture uptake, vertical density profile), as well as mechanical (internal bonding, modulus of rupture, modulus of elasticity in three-point bending) properties of particleboards, were evaluated. The results clearly show that kraft lignin can be used for the production of lignin-based adhesives for the production of particleboards.
Nová lepidla na bázi kraft-ligninu pro výrobu dřevotřískových desek
Keywords: Particleboard; Lignin; Adhesives; Urea -formaldehyde resins; Mechanical properties; Physical properties; dřevotříska; lignin; lepidla; močovinoformaldehydové pryskyřice; mechanické vlastnosti; fyzikální vlastnosti